Pengaruh Penerapan Program Membaca 15 Menit terhadap Kemampuan Literasi Siswa di SMP Negeri 15 Kota Jambi - Septevan Nanda Yudisman; Jalinur Jalinur; Rosidah Agus Mulyani (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Student literacy levels in Indonesia remain low, as reflected in national assessments and PISA studies. To address this, SMP Negeri 15 Kota Jambi implemented a 15-minute reading program before lessons as part of the School Literacy Movement (GLS). This study aims to analyze the program’s impact on students’ literacy skills using a qualitative case study approach. Informants included 10 purposively selected participants: grade VIII and IX students, Indonesian language teachers, the librarian, and the principal. Data were gathered through in-depth interviews, participatory observation, and documentation, then analyzed thematically. The results show that regular implementation of the 15-minute reading program increases students’ reading interest, broadens their knowledge, and strengthens literacy habits. It also enhances students’ readiness to learn, concentration, and engagement in other literacy activities such as book borrowing and reading discussions. Support from the principal and librarian played a key role in the program’s success, despite challenges like limited book collections and library budgets. Overall, the 15-minute reading program proves to be an effective strategy for fostering a literacy culture in junior high schools.